A methyl cellulose-based composite film with ammonia-sensitive color change, ultraviolet protection and high-energy blue light filtering functions and a preparation method thereof
Patent Information
- Application Number
- CN202611411815.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]然而,纯甲基纤维素膜在实际应用中仍存在一些局限性,例如力学强度不足、水汽阻隔性能欠佳,同时缺乏紫外线屏蔽能力、高能短波蓝光阻隔性能及氨气响应变色等功能特性,这严重制约了其在高端食品包装和紫外防护等领域的推广使用
本发明以甲基纤维素为成膜基质,通过引入柠檬酸三乙酯与功能性纳米粒子作为填料,旨在协同改善基体的力学强度、断裂伸长率、紫外阻隔效率、高能蓝光阻隔能力及氨气响应变色行为,能够突破现有的甲基纤维素膜在功能多样性方面的性能瓶颈,制备出综合性能优异的复合膜材料。所得复合膜在具有高的长期贮藏稳定性的同时,兼具优异的拉伸强度、断裂伸长率、全波段紫外线(UVA/UVB/UVC)阻隔能力、高能蓝光过滤效率以及生物可降解特性,并可通过肉眼可辨的颜色转变实时反映氨气氛围的存在,具备作为智能指示材料的潜力。
Smart Images

Figure CN122978533A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, and in particular to a methylcellulose-based composite membrane that combines ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions, as well as its preparation method. Background Technology
[0002] Traditional plastic packaging materials are difficult to degrade in the natural environment, easily causing pollution. This has prompted researchers to focus on developing environmentally friendly alternatives. Cellulose, as the most abundant natural polymer, possesses outstanding advantages such as safety, non-toxicity, biodegradability, and excellent film-forming properties. It has been widely used in many fields, including food, medicine, and chemicals, showing broad application prospects in food packaging and biodegradable packaging materials. Methylcellulose (MC), a polymer derivative derived from natural cellulose, combines good water solubility, film-forming properties, and biodegradability, making it one of the ideal matrices for constructing green packaging materials.
[0003] However, pure methylcellulose membranes still have some limitations in practical applications, such as insufficient mechanical strength, poor water vapor barrier properties, and a lack of UV shielding, high-energy short-wave blue light blocking, and ammonia-responsive color change. These limitations severely restrict their widespread use in high-end food packaging and UV protection. Therefore, there is an urgent need to develop high-performance methylcellulose-based composite materials to overcome these performance bottlenecks and expand their application areas. Summary of the Invention
[0004] The purpose of this invention is to provide a methylcellulose-based composite membrane and its preparation method that combine ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions, thereby solving the aforementioned problems in the background art. The resulting composite membrane possesses excellent tensile strength, fracture toughness, full-band ultraviolet (UVA / UVB / UVC) blocking ability, high-energy blue light filtering efficiency, long-term storage stability, and biodegradability. Furthermore, it can reflect the presence of ammonia atmosphere in real time through a color change that is visible to the naked eye, demonstrating its potential as a smart indicator material.
[0005] To achieve the above objectives, the present invention provides the following technical solution: One of the technical solutions of this invention is to provide a methylcellulose-based composite membrane that combines ammonia-sensitive color change, ultraviolet protection and high-energy blue light filtering functions, comprising the following raw materials: methylcellulose, triethyl citrate, and functional nanoparticles; wherein the mass ratio of methylcellulose, triethyl citrate and functional nanoparticles is 100:10:1-5. The preparation method of the functional nanoparticles includes the following steps: Nano-TiO2 and piperic acid were mixed in a dispersion medium and reacted to obtain a blend. The blend was then mixed with ferric sulfate to carry out a coordination complexation reaction. After solid-liquid separation, the functional nanoparticles were obtained.
[0006] Preferably, the mass ratio of nano-TiO2 to piperic acid is 30:15.41.
[0007] Preferably, the mass ratio of nano-TiO2 to ferric sulfate is 30:20.
[0008] Preferably, the reaction is carried out at a temperature of 80°C for 2 hours.
[0009] Preferably, the coordination complexation reaction is carried out at a temperature of 80°C for 20 minutes.
[0010] Preferably, the method for preparing the functional nanoparticles includes the following steps: (1) Take 0.1541 g of piperic acid, dissolve it in 30 mL of ethanol, turn on the stirrer and control the stirring speed to 500 r / min, add 0.5 mL of 1 mol / L sodium hydroxide ethanol solution to the system dropwise, and after the addition is completed, heat to 80℃ and reflux for 30 min to obtain a homogeneous solution for later use; (2) Take 0.2 g of ferric sulfate and dissolve it in a mixed solution containing 15 mL of deionized water and 15 mL of ethanol to obtain a homogeneous ferric sulfate solution for later use. (3) Take 0.3 g of nano TiO2 and disperse it in 30 mL of ethanol to obtain a uniform TiO2 dispersion for later use; (4) Add the nano TiO2 dispersion obtained in step (3) to the solution obtained in step (1), and reflux for 2 h at a stirring speed of 500 r / min and a temperature of 80℃ to obtain a uniform blend for later use. (5) Add the ferric sulfate solution obtained in step (2) to the blend obtained in step (4), reflux for 20 min at a stirring speed of 500 r / min and a temperature of 80 °C, and then centrifuge, wash with ethanol and dry to obtain the functional nanoparticles.
[0011] The second technical solution of the present invention provides a method for preparing the above-mentioned methylcellulose-based composite membrane that combines ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions, comprising the following steps: The methylcellulose, triethyl citrate, and functional nanoparticles are mixed in a dispersion medium to obtain a film-forming solution; The film-forming solution is subjected to a film-forming treatment to obtain the composite membrane.
[0012] Preferably, the film-forming treatment is a drying process after casting; the drying process is carried out at a temperature of 60°C for 12 hours.
[0013] Preferably, the dispersion medium is water.
[0014] Preferably, the method for preparing the composite membrane includes the following steps: (1) Add 2 g of methylcellulose and 0.2 g of triethyl citrate to 70 mL of deionized water and stir for 30 min at room temperature to obtain a homogeneous methylcellulose solution for later use; (2) Disperse 0.02-0.1 g of functional nanoparticles in 10 mL of deionized water and stir for 10 min at room temperature to obtain a uniform dispersion for later use; (3) Add the dispersion obtained in step (2) to the methylcellulose solution obtained in step (1), stir at room temperature for 30 min to obtain a uniform film-forming solution for later use; (4) Pour the film-forming liquid obtained in step (3) into a flat-bottomed plexiglass dish and dry it in an oven at 60°C for 12 hours to obtain the composite film.
[0015] The third technical solution of the present invention provides an application of the above-mentioned methylcellulose-based composite film with ammonia-sensitive color change, ultraviolet protection and high-energy blue light filtering functions in the field of packaging materials.
[0016] This composite film can be used in food packaging, ultraviolet / high-energy blue light protection materials, smart materials, ammonia-responsive materials, ammonia detection, environmental monitoring and safety fields.
[0017] The beneficial technical effects of the present invention are as follows: This invention uses methylcellulose as the film-forming matrix and introduces triethyl citrate and functional nanoparticles as fillers to synergistically improve the matrix's mechanical strength, elongation at break, UV blocking efficiency, high-energy blue light blocking capability, and ammonia-responsive color-changing behavior. This overcomes the performance bottleneck of existing methylcellulose membranes in terms of functional diversity, resulting in a composite membrane material with excellent comprehensive performance. The resulting composite membrane exhibits high long-term storage stability, excellent tensile strength, elongation at break, full-band UV (UVA / UVB / UVC) blocking capability, high-energy blue light filtering efficiency, and biodegradability. Furthermore, it can reflect the presence of ammonia atmosphere in real time through a visually perceptible color change, demonstrating its potential as a smart indicator material.
[0018] At the preparation level, the composite membrane boasts a simple processing technology and mild reaction conditions. The entire preparation process requires no catalyst and produces no byproducts, exhibiting high efficiency, greenness, environmental friendliness, and controllable cost, making it easy to scale up for industrial production. Based on these comprehensive properties, the composite membrane can be used as a smart indicator material to reflect the changes in freshness of meat products (such as shrimp, pork, and fish) during storage in a timely and visual manner, demonstrating broad application prospects in numerous fields such as smart food packaging, pharmaceutical packaging, ultraviolet / high-energy blue light protection, ammonia monitoring, environmental monitoring, and safety protection. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0020] Figure 1 This is a scanning electron microscope image of the functional nanoparticles of the present invention; Figure 2 This is a scanning electron microscope image of the iron-piperic acid complex particles involved in this invention; Figure 3 Scanning electron microscope (SEM) images of the brittle fracture surfaces of the pure methylcellulose membrane (a) in Comparative Example 1 and the methylcellulose-based composite membrane (b) in Example 3 of this invention; EDS images of Fe (c) and Ti (d) in the brittle fracture surface of the methylcellulose-based composite membrane in Example 3; Figure 4 The images show the initial physical photograph (a) and the discolored physical photograph (b) of the methylcellulose-based composite membrane sample in Example 3 of the present invention after ammonia fumigation. Figure 5 The image shows a comparison of the color difference stability of the membrane materials of Examples 1-3 and Comparative Example 1 after storage at 25°C and 57% relative humidity for 30 days. Detailed Implementation
[0021] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0022] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, are also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0023] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. It should be noted that any aspects of this invention not described in detail are conventional practices in the art and are not the focus of this invention.
[0024] The terms “comprising,” “including,” “having,” “containing,” etc., used in this invention are all open-ended terms, meaning that they include but are not limited to.
[0025] In the following embodiments and comparative examples of this invention, piperic acid was a product provided by Aladdin Reagent Co., Ltd. (CAS No.: 94-53-1); nano-TiO2 was a product provided by Ron Reagent Co., Ltd. (CAS 13463-67-7, specification: Jin Hong hydrophilic high-purity reagent, with a diameter of 40 nm); triethyl citrate was a product provided by Shanghai Yuanye Biotechnology Co., Ltd. (CAS 77-93-0); methylcellulose was a product provided by Shanghai Aladdin Biochemical Technology Co., Ltd. (with a methoxy content of 28% and a number-average molecular weight of 55000 g / mol); ferric sulfate was a product provided by Xilong Scientific Co., Ltd. (CAS No.: 10028-22-5); and ethanol was an analytical grade reagent provided by Tianjin Fuyu Fine Chemical Co., Ltd. Furthermore, the acrylic dishes used in the following embodiments and comparative examples of this invention are square flat-bottomed acrylic dishes with dimensions of 13cm × 13cm (dish height 1.5 cm).
[0026] The preparation method of the functional nanoparticles used in the following embodiments and comparative examples of the present invention is as follows: (1) Take 0.1541 g of piperic acid, dissolve it in 30 mL of ethanol, turn on the stirrer and control the stirring speed to 500 r / min, add 0.5 mL of 1 mol / L sodium hydroxide ethanol solution to the system dropwise, and after the addition is completed, heat to 80℃ and reflux for 30 min to obtain a homogeneous solution for later use; (2) Take 0.2 g of ferric sulfate and dissolve it in a mixed solution containing 15 mL of deionized water and 15 mL of ethanol to obtain a homogeneous ferric sulfate solution for later use. (3) Take 0.3 g of nano TiO2 and disperse it in 30 mL of ethanol to obtain a uniform TiO2 dispersion for later use; (4) Add the nano TiO2 dispersion obtained in step (3) to the solution obtained in step (1), and reflux for 2 h at a stirring speed of 500 r / min and a temperature of 80℃ to obtain a uniform blend for later use. (5) Add the ferric sulfate solution obtained in step (2) to the blend obtained in step (4), reflux for 20 min at a stirring speed of 500 r / min and a temperature of 80℃, and then centrifuge, wash with ethanol and dry to obtain functional nanoparticles (the main particle size distribution range is 50-100 nm).
[0027] Unless otherwise specified, "room temperature" in this invention refers to 20±10℃.
[0028] All raw materials used in the following embodiments and comparative examples of the present invention are commercially available products.
[0029] The technical solution of the present invention will be further described below through embodiments.
[0030] Example 1 A methylcellulose-based composite membrane that combines ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions has methylcellulose, triethyl citrate, and functional nanoparticles in a mass ratio of 100:10:1 as its core raw materials.
[0031] The preparation method is as follows: (1) Add 2 g of methylcellulose and 0.2 g of triethyl citrate to 70 mL of deionized water and stir for 30 min at room temperature to obtain a homogeneous methylcellulose solution for later use; (2) Disperse 0.02 g of functional nanoparticles in 10 mL of deionized water and stir for 10 min at room temperature to obtain a uniform dispersion for later use; (3) Add the dispersion obtained in step (2) to the methylcellulose solution obtained in step (1), stir at room temperature for 30 min to obtain a uniform film-forming solution for later use; (4) Pour the film-forming liquid obtained in step (3) into a flat-bottomed plexiglass dish and dry it in an oven at 60°C for 12 hours to obtain a methylcellulose-based composite membrane that combines ammonia-sensitive color change, ultraviolet protection and high-energy blue light filtering functions.
[0032] Example 2 A methylcellulose-based composite membrane that combines ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions has methylcellulose, triethyl citrate, and functional nanoparticles in a mass ratio of 100:10:3 as its core raw materials.
[0033] The preparation method is as follows: (1) Add 2 g of methylcellulose and 0.2 g of triethyl citrate to 70 mL of deionized water and stir for 30 min at room temperature to obtain a homogeneous methylcellulose solution for later use; (2) Disperse 0.06 g of functional nanoparticles in 10 mL of deionized water and stir for 10 min at room temperature to obtain a uniform dispersion for later use; (3) Add the dispersion obtained in step (2) to the methylcellulose solution obtained in step (1), stir at room temperature for 30 min to obtain a uniform film-forming solution for later use; (4) Pour the film-forming liquid obtained in step (3) into a flat-bottomed plexiglass dish and dry it in an oven at 60°C for 12 hours to obtain a methylcellulose-based composite membrane that combines ammonia-sensitive color change, ultraviolet protection and high-energy blue light filtering functions.
[0034] Example 3 A methylcellulose-based composite membrane that combines ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions has methylcellulose, triethyl citrate, and functional nanoparticles in a mass ratio of 100:10:5 as its core raw materials.
[0035] The preparation method is as follows: (1) Add 2 g of methylcellulose and 0.2 g of triethyl citrate to 70 mL of deionized water and stir for 30 min at room temperature to obtain a homogeneous methylcellulose solution for later use; (2) Disperse 0.1 g of functional nanoparticles in 10 mL of deionized water and stir for 10 min at room temperature to obtain a uniform dispersion for later use; (3) Add the dispersion obtained in step (2) to the methylcellulose solution obtained in step (1), stir at room temperature for 30 min to obtain a uniform film-forming solution for later use; (4) Pour the film-forming liquid obtained in step (3) into a flat-bottomed plexiglass dish and dry it in an oven at 60°C for 12 hours to obtain a methylcellulose-based composite membrane that combines ammonia-sensitive color change, ultraviolet protection and high-energy blue light filtering functions.
[0036] Example 4 (Higher proportion of functional nanoparticles) A methylcellulose-based composite membrane that combines ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions has methylcellulose, triethyl citrate, and functional nanoparticles in a mass ratio of 100:10:7 as its core raw materials.
[0037] The preparation method is as follows: (1) Add 2 g of methylcellulose and 0.2 g of triethyl citrate to 70 mL of deionized water and stir for 30 min at room temperature to obtain a homogeneous methylcellulose solution for later use; (2) Disperse 0.14 g of functional nanoparticles in 10 mL of deionized water and stir for 10 min at room temperature to obtain a uniform dispersion for later use; (3) Add the dispersion obtained in step (2) to the methylcellulose solution obtained in step (1), stir at room temperature for 30 min to obtain a uniform film-forming solution for later use; (4) Pour the film-forming liquid obtained in step (3) into a flat-bottomed plexiglass dish and dry it in an oven at 60°C for 12 hours to obtain a methylcellulose-based composite membrane that combines ammonia-sensitive color change, ultraviolet protection and high-energy blue light filtering functions.
[0038] Comparative Example 1 The only difference from Example 3 is that a pure methylcellulose membrane without triethyl citrate and functional nanoparticles was prepared, and the steps are as follows: (1) Add 2 g of methylcellulose to 70 mL of deionized water and stir for 30 min at room temperature to obtain a homogeneous methylcellulose solution for later use; (2) Add 10 mL of deionized water to the methylcellulose solution obtained in step (1) and stir for 10 min at room temperature to obtain a uniform film-forming solution for later use. (3) Pour the film-forming solution obtained in step (2) into a flat-bottomed plexiglass dish and dry it in an oven at 60°C for 12 hours to obtain a pure methylcellulose membrane without triethyl citrate and functional nanoparticles.
[0039] Comparative Example 2 The only difference from Example 3 is that the methylcellulose / triethyl citrate composite membrane without functional nanoparticles was prepared using the following steps: (1) Add 2 g of methylcellulose and 0.2 g of triethyl citrate to 70 mL of deionized water and stir for 30 min at room temperature to obtain a homogeneous methylcellulose solution for later use; (2) Add 10 mL of deionized water to the methylcellulose solution obtained in step (1) and stir for 10 min at room temperature to obtain a uniform film-forming solution for later use. (3) Pour the film-forming liquid obtained in step (2) into a flat-bottomed plexiglass dish and dry it in an oven at 60°C for 12 hours to obtain a methylcellulose / triethyl citrate composite film without functional nanoparticles.
[0040] Comparative Example 3 The only difference from Example 3 is that the methylcellulose / functional nanoparticle composite membrane without triethyl citrate was prepared using the following steps: (1) Add 2 g of methylcellulose to 70 mL of deionized water and stir for 30 min at room temperature to obtain a homogeneous methylcellulose solution for later use; (2) Disperse 0.1 g of functional nanoparticles in 10 mL of deionized water and stir for 10 min at room temperature to obtain a uniform dispersion for later use; (3) Add the dispersion obtained in step (2) to the methylcellulose solution obtained in step (1), stir at room temperature for 30 min to obtain a uniform film-forming solution for later use; (4) Pour the film-forming liquid obtained in step (3) into a flat-bottomed plexiglass dish and dry it in an oven at 60°C for 12 hours to obtain a methylcellulose / functional nanoparticle composite film without triethyl citrate.
[0041] Comparative Example 4 The only difference from Example 3 is that triethyl citrate in Example 3 is replaced with glycerol to prepare the methylcellulose / glycerol / functional nanoparticle composite membrane. The steps are as follows: (1) Add 2 g of methylcellulose and 0.2 g of glycerol to 70 mL of deionized water and stir for 30 min at room temperature to obtain a homogeneous methylcellulose solution for later use; (2) Disperse 0.1 g of functional nanoparticles in 10 mL of deionized water and stir for 10 min at room temperature to obtain a uniform dispersion for later use; (3) Add the dispersion obtained in step (2) to the methylcellulose solution obtained in step (1), stir at room temperature for 30 min to obtain a uniform film-forming solution for later use; (4) Pour the film-forming solution obtained in step (3) into a flat-bottomed plexiglass dish and dry it in an oven at 60°C for 12 hours to obtain a methylcellulose / glycerol / functional nanoparticle composite film.
[0042] Comparative Example 5 The only difference from Example 3 is that triethyl citrate in Example 3 is replaced with urea to prepare the methylcellulose / urea / functional nanoparticle composite membrane. The steps are as follows: (1) Add 2 g of methylcellulose and 0.2 g of urea to 70 mL of deionized water and stir for 30 min at room temperature to obtain a homogeneous methylcellulose solution for later use; (2) Disperse 0.1 g of functional nanoparticles in 10 mL of deionized water and stir for 10 min at room temperature to obtain a uniform dispersion for later use; (3) Add the dispersion obtained in step (2) to the methylcellulose solution obtained in step (1), stir at room temperature for 30 min to obtain a uniform film-forming solution for later use; (4) Pour the film-forming solution obtained in step (3) into a flat-bottomed plexiglass dish and dry it in an oven at 60°C for 12 hours to obtain a methylcellulose / urea / functional nanoparticle composite film.
[0043] Comparative Example 6 The only difference from Example 3 is that the functional nanoparticles in Example 3 are replaced with iron-piperic acid complex particles to prepare the methylcellulose / triethyl citrate / iron-piperic acid complex particle composite membrane. The steps are as follows: (1) Add 2 g of methylcellulose and 0.2 g of triethyl citrate to 70 mL of deionized water and stir for 30 min at room temperature to obtain a homogeneous methylcellulose solution for later use; (2) Disperse 0.1 g of iron-piperic acid complex particle packing in 10 mL of deionized water and stir for 10 min at room temperature to obtain a uniform dispersion for later use; (3) Add the dispersion obtained in step (2) to the methylcellulose solution obtained in step (1), stir at room temperature for 30 min to obtain a uniform film-forming solution for later use; (4) Pour the film-forming solution obtained in step (3) into a flat-bottomed plexiglass dish and dry it in an oven at 60°C for 12 hours to obtain a methylcellulose / triethyl citrate / iron-piperic acid complex particle composite film.
[0044] The preparation steps of the iron-piperic acid complex particles are as follows: (1) Take 0.1541 g of piperic acid, dissolve it in 30 mL of ethanol, turn on the stirrer and control the stirring speed to 500 r / min, add 0.5 mL of 1 mol / L sodium hydroxide ethanol solution to the system dropwise, and after the addition is completed, heat to 80℃ and reflux for 30 min to obtain a homogeneous solution for later use; (2) Take 0.2 g of ferric sulfate and dissolve it in a mixed solution containing 15 mL of deionized water and 15 mL of ethanol to obtain a homogeneous ferric sulfate solution for later use. (3) Add 30 mL of ethanol to the solution obtained in step (1) and reflux for 2 h at a stirring speed of 500 r / min and a temperature of 80 °C to obtain a homogeneous blend for later use. (4) Add the ferric sulfate solution obtained in step (2) to the blend obtained in step (3), reflux for 20 min at a stirring speed of 500 r / min and a temperature of 80℃, and then centrifuge, wash with ethanol and dry to obtain iron-piperic acid complex particles (average particle size of ~2.4 μm).
[0045] Structural and performance testing: 1) The morphology of functional nanoparticles, iron-piperic acid complex particles and membrane samples was characterized by scanning electron microscopy. Figure 1 The functional nanoparticles prepared by this invention are uniform small-sized particles with a main particle size distribution range of 50-100 nm (obtained by statistical calculation using ImageJ software). Figure 2 The iron-piperic acid complex particles involved in this invention are uniform microparticles with an average particle size of ~2.4 μm (obtained by statistical calculation using ImageJ software). Figure 3 a and b are scanning electron microscope images of the brittle fracture surfaces of the pure methylcellulose membrane obtained in Comparative Example 1 and the methylcellulose-based composite membrane obtained in Example 3 of the present invention, respectively. Figure 3 c and d are EDS (Energy Dispersive X-ray Difference) mapping diagrams of Fe and Ti elements in the brittle fracture surface of the methylcellulose-based composite film in Example 3, respectively. Figure 3 It can be observed that the functional nanoparticles in the composite membrane have good dispersibility, which is beneficial to the overall improvement of the membrane material's mechanical, barrier properties and functional characteristics.
[0046] 2) The mechanical and optical properties of the membrane materials prepared in Comparative Examples 1-6 and Examples 1-4 of this invention were tested. The ultraviolet-visible properties were tested using an ultraviolet-visible spectrophotometer (Shimadzu UV-2450), and the average ultraviolet transmittance was calculated according to GB / T18830-2009. The tensile properties were tested according to GB / T 1040-2006.
[0047] Regarding mechanical properties, the results in Table 1 show that the tensile strength and elongation at break of the pure methylcellulose membrane prepared in Comparative Example 1 were 70.8 MPa and 15.3%, respectively. In Comparative Example 2, after adding only triethyl citrate to the methylcellulose matrix, the tensile strength of the resulting composite membrane decreased to 67.9 MPa, while the elongation at break increased to 18.4%, indicating that triethyl citrate can act as a plasticizer to improve the ductility of the methylcellulose membrane. In Examples 1-3, the tensile strength and elongation at break of the membrane significantly increased after the simultaneous addition of triethyl citrate and an appropriate amount of functional nanoparticles; especially in Example 3, the resulting composite membrane exhibited the highest tensile strength while maintaining a high elongation at break (i.e., ductility). Compared to Example 3, in Example 4, after further increasing the amount of functional nanoparticles, the tensile strength and elongation at break of the membrane significantly decreased, indicating that excessive functional nanoparticle filler leads to a decrease in the mechanical properties of the membrane material. Furthermore, in Comparative Example 3, the tensile strength and elongation at break of the composite membrane were significantly reduced after only adding functional nanoparticle fillers to the methylcellulose matrix. By comparing the mechanical properties of the membrane materials in Example 3 and Comparative Examples 1-3, it can be seen that adding triethyl citrate and functional nanoparticles separately to the methylcellulose membrane matrix cannot effectively improve the tensile strength and elongation at break simultaneously. However, adding triethyl citrate and functional nanoparticles simultaneously to the methylcellulose membrane matrix can synergistically give the membrane material high tensile strength and elongation at break (i.e., ductility). Additionally, replacing triethyl citrate in Example 3 with glycerol and urea respectively, the resulting methylcellulose / glycerol / functional nanoparticle composite membrane (Comparative Example 4) and methylcellulose / urea / functional nanoparticle composite membrane (Comparative Example 5) both showed significant improvements in elongation at break, but both showed a significant decrease in tensile strength. Furthermore, after replacing the functional nanoparticles in Example 3 with iron-piperic acid complex particles, the prepared methylcellulose / triethyl citrate / iron-piperic acid complex particle composite film (i.e., Comparative Example 6) showed a significant improvement in elongation at break, but a significant decrease in tensile strength.
[0048] Table 1. Mechanical and optical properties of the film materials obtained in Comparative Examples 1-6 and Examples 1-4 3) The ammonia response test method is as follows: The membrane material is pre-cut into samples with a diameter of 1 cm and fixed in a sealed container with a diameter of 10 cm and a height of 10 cm. 10 mL of 25% ammonia water is added to the sealed container. The sample is 5 cm away from the surface of the ammonia water. The container is sealed to form an ammonia reaction environment. The container is left to stand for 60 min. Then the color change of the membrane material is observed and recorded.
[0049] The ammonia response test results showed that the pure methylcellulose membrane prepared in Comparative Example 1 was initially colorless and transparent. After being exposed to an ammonia environment, the membrane color did not change and remained colorless and transparent, indicating that it did not possess the ability to change color in response to ammonia. In contrast, the composite membrane of Example 1 was initially light yellow, changing to pale yellow after ammonia exposure; the composite membrane prepared in Example 2 was initially pale yellow, changing to yellow after ammonia exposure; and the composite membrane prepared in Example 3 was initially yellow (see...). Figure 4 (a) Ammonia turns reddish-brown upon exposure (see a) Figure 4 (b). It can be seen that as the amount of functional nanoparticles added increases, the initial color of the composite film gradually deepens, and the color change response after ammonia exposure also becomes more significant, indicating that the ammonia-sensitive color change performance of the composite film is positively correlated with the loading of functional nanoparticles.
[0050] 4) The method for testing the color stability during long-term storage is as follows: The membrane sample (1 cm in diameter) is stored at 25℃ and 57% humidity for 30 days. The color change of the membrane sample is then observed and measured using a colorimeter (NR200, Shenzhen Sanenshi Co., Ltd.), and the color difference ΔE after storage is calculated. ,in, , and This is the initial color value of the membrane sample. , and This is the color value of the membrane sample after storage (Note: , and The values are the core parameters for measuring color in a colorimeter, representing lightness, red-green axis, and yellow-blue axis, respectively.
[0051] The results of the long-term storage color stability test of Comparative Example 1 and Examples 1-3 (see) Figure 5 The results demonstrate that the membrane materials prepared in Examples 1, 2, and 3, after being stored at 25°C and 57% humidity for 30 days, did not exhibit significant color changes, and the color difference ΔE value after storage was less than 2 (i.e., the color difference was imperceptible to the human eye). These results indicate that the membrane materials prepared according to this invention possess excellent long-term storage stability.
[0052] 5) Shrimp Freshness Monitoring Experiment: Fresh shrimp were purchased from the market. Shrimp of uniform size and weight were selected and divided into two groups of 4 shrimp each, with a total weight of 30g per group. The shrimp were placed in Petri dishes and sealed with the dish lids. The bottom of the petri dish lids of the two treatment groups was covered with a pure methylcellulose membrane prepared in Comparative Example 1 and a methylcellulose-based composite membrane prepared in Example 3 (pre-cut into circular sample membranes with a diameter of 1 cm). The above devices were then stored in an oven at 25°C. The changes in shrimp freshness and the color response of the indicator membrane were observed and recorded at regular intervals.
[0053] The results in Table 2 show that the shrimp samples deteriorated significantly after 24 hours of storage. At this time, the methylcellulose-based composite membrane sample involved in Example 3 changed from its initial yellow color to black. This can be attributed to the reaction between the hydrogen sulfide released by the deteriorated shrimp and the iron on the surface of the particle filler in the composite membrane, which produced black iron sulfide and other products.
[0054] Table 2 Results of shrimp freshness monitoring experiment (where t is the storage time of fresh shrimp) In summary, the sample performance test data (see Tables 1 and 2) show that the methylcellulose-based composite membrane prepared in this invention, which combines ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions, possesses excellent mechanical strength, elongation at break, ultraviolet shielding performance, high-energy blue light blocking ability, long-term storage stability, and biodegradability. It can be used as a smart indicator material to effectively and promptly indicate changes in the freshness of shrimp and other meat products during storage. Furthermore, the composite material has a simple processing technology, mild reaction conditions, requires no organic solvents, is environmentally friendly, has controllable costs, and is easy to scale up. It shows broad application prospects in many fields such as smart food packaging, smart responsive materials, ultraviolet / high-energy blue light protection, biomedicine, environmental monitoring, and safety protection.
[0055] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A methylcellulose-based composite membrane possessing ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions, characterized in that, It includes the following raw materials: methylcellulose, triethyl citrate, and functional nanoparticles; the mass ratio of methylcellulose, triethyl citrate, and functional nanoparticles is 100:10:1-5. The preparation method of the functional nanoparticles includes the following steps: Nano-TiO2 and piperic acid were mixed in a dispersion medium and reacted to obtain a blend. The blend was then mixed with ferric sulfate to carry out a coordination complexation reaction. After solid-liquid separation, the functional nanoparticles were obtained.
2. The methylcellulose-based composite membrane with ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions as described in claim 1, characterized in that, The mass ratio of nano-TiO2 to piperic acid is 30:15.
41.
3. The methylcellulose-based composite membrane with ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions as described in claim 1, characterized in that, The mass ratio of nano-TiO2 to ferric sulfate is 30:
20.
4. The methylcellulose-based composite membrane with ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions as described in claim 1, characterized in that, The reaction was carried out at a temperature of 80°C for 2 hours.
5. The methylcellulose-based composite membrane with ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions as described in claim 1, characterized in that, The coordination complexation reaction was carried out at a temperature of 80°C for 20 minutes.
6. A method for preparing a methylcellulose-based composite membrane with ammonia-sensitive color change, ultraviolet protection, and high-energy blue light filtering functions as described in any one of claims 1-5, characterized in that, Includes the following steps: The methylcellulose, triethyl citrate, and functional nanoparticles are mixed in a dispersion medium to obtain a film-forming solution; The film-forming solution is subjected to a film-forming treatment to obtain the composite membrane.
7. The preparation method according to claim 6, characterized in that, The film-forming process involves drying after casting; the drying process is carried out at a temperature of 60°C for 12 hours.
8. The preparation method according to claim 6, characterized in that, The dispersion medium is water.
9. The application of a methylcellulose-based composite film with ammonia-sensitive color change, ultraviolet protection and high-energy blue light filtering functions as described in any one of claims 1-5 in the field of packaging materials.
Citation Information
Patent Citations
Air separator
CA94531A